Analyzing Benthic Distribution and Public Infrastructure to Support Tourism Zoning on Tunda Island - Subiyanto; Abdurrahman, Umar; Khadami, Faruq; Anwar, Iwan Pramesti (Research Collaboration Community (Rescollacom), 2025)
This study presents a comprehensive analysis of benthic habitat distribution and public infrastructure on Tunda Island, aimed at developing effective tourism zoning strategies. By integrating high-resolution spatial data derived from field surveys and remote sensing technologies, including multispectral imagery and Geographic Information System (GIS) methodologies, the research delineates distinct zones optimal for diverse tourism activities. The findings indicate that the southern and southeastern parts of the island, characterized by sandy substrates and proximity to resorts and docks, are well-suited for intensive tourism. Conversely, the northern and northwestern regions, dominated by coral and rocky substrates, are proposed for conservation-oriented educational tourism due to their rich biodiversity. The research also highlights the potential of community-based tourism facilitated by existing public infrastructure such as schools and mosques, which supports local engagement in tourism development. The resultant zoning map serves as a vital tool for local authorities and stakeholders in Tunda Island, guiding sustainable tourism management practices that value ecological integrity and community involvement. This study underscores the importance of interdisciplinary approaches in ecological monitoring and tourism planning, contributing to the broader discourse on sustainable practices in small island contexts